Health facility and health worker readiness to deliver new national treatment policy for malaria in Kenya. - Njogu, J; Akhwale, W; Hamer, D; Zurovac, D (2008)
OBJECTIVE: To evaluate health facility and health worker readiness to deliver new artemether-lumefantrine (AL) treatment policy for uncomplicated malaria in Kenya. DESIGN: Cross-sectional survey. SETTING: Health facilities in four sentinel districts in Kenya. PARTICIPANTS: All government facilities in study districts (n = 211) and all health workers performing outpatient consultations (n = 654). MAIN OUTCOME MEASURES: Availability of antimalarial drugs on the survey day, stock-outs in past six months, presence of AL wall charts, health worker's exposure to in-service training on AL and access to new national malaria guidelines. RESULTS: The availability of any tablets of AL, sulfadoxine-pyrimethamine and amodiaquine was nearly universal on the survey day. However, only 61% of facilities stocked all four weight-specific packs of AL. In the past six months, 67% of facilities had stock-out of at least one AL tablet pack and 15% were out of stock for all four packs at the same time. Duration of stock-out was substantial for all AL packs (median range: 27-39% of time). During the same period, the stock-outs of sulfadoxine-pyrimethamine and amodiaquine were rare. Only 19% of facilities had all AL wall charts displayed, AL in-service training was provided to 47% of health workers and 59% had access to the new guidelines. CONCLUSION: Health facility and health worker readiness to implement AL policy is not yet optimal. Continuous supply of all four AL pack sizes and removal of not recommended antimalarials is needed. Further coordinated efforts through the routine programmatic activities are necessary to improve delivery of AL at the point of care.